Investigating the effect of counter flow formation, ribs and dimples on the hydrothermal performance of the serpentine Mini-Channel Heat Sink (SMCHS). (December 2022) - Mahmood, Hind; Freegah, Basim
Abstract: The objectives of the current study are to clarify the influence of counter flow formation and ribs with dimples on hydrothermal performance and base temperature distribution of serpentine mini-channel heat sink (SMCHS). The numerical part of the study is done by a simulation process with Computational Fluid Dynamics (CFD) software (ANSYS Fluent 19R3). The considered models are; traditional model, Model (A) with inlet at center of heat sink and straight SMCHS flow formation, Models (B) having straight SMCHS and two inlets and two outlets with counter flow, Model (C) having straight SMCHS with counter flow and ribs with dimples (distance between ribs and dimples is 5 mm, ribs diameter is 1 mm and dimples diameter is 2.29 mm). The comparison between experimental and numerical results shows good agreement. The results show that the Nusselt number, pressure drop, thermal resistance, temperature distribution, and the Overall Performance Factor (OPF) have all significantly improved as a result of all the factors under consideration. All new models have OPF more than unity as compared to the traditional model. Also the results depict that model (C) is the best model with uniform base temperature distribution and OPF of 1.91 as compared to the traditional model. Highlights: New models of SMCHS are proposed, namely counter flow formation with ribs and dimples. Enhancement of hydrothermal performance by placing the flow entrance at the center. The surface area is increased by the ribs and dimples. The optimal performance achieved in model -C- which has the best uniformity of temperature distribution with OPF 1.91.